Life Experiences of Borderline Personality Disorder Survivors in the Recovery Process: A Qualitative Study - Endah Sarwendah Sarwendah; Suryani Suryani; Efri Widianti (Jurnal Keperawatan Padjadjaran, 2022)
Background: Borderline Personality Disorder (BPD) is a personality disorder with the main symptoms of emotional instability, impulsive behavior, negative self-concept, and impaired interpersonal function. Recovery in BPD is directed at the existence of satisfaction and meaning in life even with limited conditions due to symptoms of the disorder that still exists. Purpose: The aim of this study is to explore the life experiences of BPD survivors in their recovery process. Methods: This research is a qualitative research with a phenomenological approach. In-depth interviews were conducted with 10 BPD survivors from the Indonesian BPD Community. The research was conducted from August to November 2021 and interviews were conducted using Zoom Meeting. Interview transcripts were analyzed using the Colaizzi method. Results: Six themes were extracted in this study, namely, the recovery process is not found alone, difcult to understand and love oneself, difcult to build stable relationships with others, journey to peace with oneself, the most painful experience that comes from the closest people and the experience of mental health services in Indonesia. Conclusion:The process of self-identification is the first step in the recoveryprocess in an individual’s journey with BPD. The available support systemhelps BPD survivors to be able to adapt to the experience resulting fromBPD symptoms. It is necessary to increase the knowledge of nurses aboutBPD in order to be able to provide good nursing care.